Validity of Gray Scale Sonography along with Color Doppler Spectral Analysis for the detection of Malignant Breast Tumour - Ara, Showkat; Jesmin, Sabina; Sattar, AFM Arshedi; Akhter, SM Quamrul; Jahan, Waseka Akhter; Kabir, AKM Golam; Kamal, Syed Md Sazzad (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Detection of mass in the breastis very essential for the early treatment. Objective: The purpose of the present study was to validate the Doppler sonography to detect the pathological lesions of breast. Methodology: This cross sectional study was carried out in the Department of Radiology and Imaging in collaboration with the Department of Surgery and Department of Pathology at Banghabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from July 2008 to June 2009 for a period of one (01) year. Clinically suspected women with breast mass who were attended in the OPD or inpatient department were selected purposively as study population. All the patients were examined by 2-D Real-Time B-Mode Ultrasonography by using high frequency (7.5 MHz) linear transducer. Blood flow was studied using Duplex sonography in which Gray scale 2D sonography was combined with Pulsed Doppler. Test of validity was done for color Doppler Sonographic findings in evaluation of benign and malignant breast lesion. Result:A total number of 50 cases were recruited for this study. Out of 50 cases,25 cases true positive, 1 false negative, 2 false positive, 22 true negative confirmed by histopathology. Here sensitivity and specificity of color Doppler ultrasonography are 92.59% and 86.95% respectively. Here accuracy of color Doppler study is 90.0% and the positive predictive value was 89.28% and negative predictive value was 90.9%. Conclusion: Color Doppler Ultrasonography is a useful imaging method in the differentiation between benign and malignant breast masses. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 10-13